2013
DOI: 10.1155/2013/392010
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Plasma Exposure and Lung Distribution of Two Human Use Commercial Azithromycin Formulations Assessed in Murine Model: A Preclinical Study

Abstract: Azithromycin (AZM) therapeutic failure and relapses of patients treated with generic formulations have been observed in clinical practice. The main goal of this research was to compare in a preclinical study the serum exposure and lung tissue concentration of two commercial formulations AZM-based in murine model. The current study involved 264 healthy Balb-C. Mice were divided into two groups (n = 44): animals of Group A (reference formulation -R-) were orally treated with AZM suspension at 10 mg/kg of b.w. Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…For this analysis, animal lung concentration data were available for anidulafungin (rat), bazedoxifene (rat), chloroquine (3 albino rat studies), favipiravir (monkey), hydroxychloroquine (2 albino rat studies), nitazoxanide (mouse), tamoxifen (rat), cyclosporine (rat), ritonavir (rat), azithromycin (mouse), dolutegravir (mouse), gilteritinib (albino rat), and lopinavir (rat). [23][24][25][26][27][28][29][30][31][32] Agreement between the predicted and measured K p was assessed by simple linear regression and by constructing Bland-Altman plots, the limits of agreement (mean ± 2 SD) were included in these plots as previously described. 33…”
Section: Data Analysis and Interpretationmentioning
confidence: 99%
“…For this analysis, animal lung concentration data were available for anidulafungin (rat), bazedoxifene (rat), chloroquine (3 albino rat studies), favipiravir (monkey), hydroxychloroquine (2 albino rat studies), nitazoxanide (mouse), tamoxifen (rat), cyclosporine (rat), ritonavir (rat), azithromycin (mouse), dolutegravir (mouse), gilteritinib (albino rat), and lopinavir (rat). [23][24][25][26][27][28][29][30][31][32] Agreement between the predicted and measured K p was assessed by simple linear regression and by constructing Bland-Altman plots, the limits of agreement (mean ± 2 SD) were included in these plots as previously described. 33…”
Section: Data Analysis and Interpretationmentioning
confidence: 99%
“…Studies by some researchers, have shown that Azithromycin concentrations are highly accumulated in alveolar macrophages and lung which is 100% higher than that reported in plasma [ 23 , 30 ]. Based on these studies, Azithromycin has been largely recommended for the treatment of some respiratory diseases, sexually transmitted diseases, some skin diseases, and otitis media [ 23 , 31 ]. Among other reasons, this antibiotic formulated mainly as suspension or tablets is used in human and in veterinary medicine [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, we used a higher dose monotherapy of AZM (91 mg/kg/day) and found no reproducible antiviral effect, with unmodified lung infectious titres and viral RNA yields, and no improvement of pulmonary histopathological impairments. The good pulmonary diffusion of the molecule has been well documented in several animal models ( Davila et al, 1991 ; Resendiz et al, 2020 ; Rivulgo et al, 2013 ). In particular, a study assessed the lung diffusion of the drug after a single oral intake of 50 mg/kg in Syrian hamsters.…”
Section: Discussionmentioning
confidence: 93%